2022
DOI: 10.1246/cl.210809
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dinaphtho[2,1-a:2,3-f]pentalene: A Stable Antiaromatic/Quinoidal Hydrocarbon Showing Appropriate Carrier Mobility in the Amorphous Layer

Abstract: A stable diareno[a,f]pentalene, dinaphtho[2,1-a:2,3-f]pentalene 6, was synthesized and characterized. The nonsymmetrical dinaphtho-fused structure of 6 highly localized the π-electrons on the pentalene core, creating a quinoidal closed-shell singlet state with a weakened antiaromatic nature. Due to the relatively high HOMO level and the presence of CH–π contacts, the mesityl derivative 6b exhibited a hole mobility of 4.37 × 10−4 cm2 V−1 s−1, as measured by a space-charge-limited current (SCLC) method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…28 Although sulfur-embedded small polycyclic aromatic system was reported to show good SCLC hole mobility (8.72 × 10 −2 cm 2 · V −1 · s −1 ), 25a hydrocarbon motifs like antiaromatic diareno-pentalene showed low hole-carrier mobility (4.37 × 10 −4 cm 2 · V −1 · s −1 ) under the SCLC method. 29 Considering [2,1- c ]IF as a benzo-interpositioned 30 pentalene system, our studies on the symmetrical or unsymmetrical [2,1- c ]IFs 1 , 7 , 8 and 17 π-systems revealed an order of magnitude greater charge-carrier mobility for both holes and electrons. Moreover, a balanced ambipolar charge-transport behavior could be extracted for the first time.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…28 Although sulfur-embedded small polycyclic aromatic system was reported to show good SCLC hole mobility (8.72 × 10 −2 cm 2 · V −1 · s −1 ), 25a hydrocarbon motifs like antiaromatic diareno-pentalene showed low hole-carrier mobility (4.37 × 10 −4 cm 2 · V −1 · s −1 ) under the SCLC method. 29 Considering [2,1- c ]IF as a benzo-interpositioned 30 pentalene system, our studies on the symmetrical or unsymmetrical [2,1- c ]IFs 1 , 7 , 8 and 17 π-systems revealed an order of magnitude greater charge-carrier mobility for both holes and electrons. Moreover, a balanced ambipolar charge-transport behavior could be extracted for the first time.…”
Section: Resultsmentioning
confidence: 86%
“…Mp: 55 -56 °C. 1 H NMR (400 MHz, CDCl 3 ): δ 9.92 -9.86 (m, 1 H), 8.17 (29). Under a nitrogen atmosphere, in 10 mL dry THF solution of 27 (162 mg, 0.43 mmol), (3,5-bis(trifluoromethyl)phenyl)magnesium bromide (prepared from 1-bromo-3,5-bis(trifluoromethyl)benzene (0.37 mL, 2.15 mmol) and magnesium turning (63 mg, 2.58 mmol) in dry THF (5 mL)) was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
“…It is of substantial interest to utilize s -indacene derivatives as organic semiconductors in solution-processed OFET devices with an aim to unveil the relationships among molecular structure, solid state packing, and charge transport properties of antiaromatic compounds. The congeners of DBP and [1,2- b ]­IF that have been employed for OFETs are regarded as pentalene- and s -indacene-based materials, respectively. Nevertheless, up to now, an intrinsic tricyclic s -indacene derivative has never been evaluated in OFETs. Here we selected hexaxylyl derivative 1f which is endowed with stability and solution processability for a preliminary OFET application.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of antiaromaticity was established many decades ago for prototypical monocyclic hydrocarbons of 4 n π-electrons. , However, polycyclic antiaromatic hydrocarbons (PAAHs) have attracted renewed interest during the last two decades in view of new criteria of antiaromaticity and small energy gaps between HOMO/LUMO levels and the Fermi level, which are relevant to open-shell character , and carrier mobility in organic field-effect transistors (OFETs). Among PAAHs, dibenzo­[ a , e ]­pentalene (DBP) and indeno­[1,2- b ]­fluorene ([1,2- b ]­IF) (Figure a), which belong to nonalternant hydrocarbons bearing five-membered rings, have been intensively investigated as stable singlet diradicals and building blocks , for conjugated polymers and macrocyclic molecules of unique topology and for optoelectronic applications. These are environmentally stable due to benzo fusion to 8 π-electron pentalene and 12 π-electron s -indacene ( 1a ), , respectively, which are highly reactive without steric protection. However, PAAHs without benzo fusion have never been exploited for systematic study of their structure and physical properties and, needless to say, for materials applications. We envisioned that hexaaryl derivatives of s -indacene ( 1a ) would be stable enough for such purposes in view of the weak antiaromaticity and moderate open-shell character ,, theoretically predicted for 1a .…”
Section: Introductionmentioning
confidence: 99%
“…16,50,51 From this perspective, we have recently focused on diareno[a,f ]pentalenes 52−54 and disclosed the interrelation between their antiaromatic and open-shell characteristics, 55,56 showing hole transport behavior. 57 In a series of diareno[a,f ]pentalenes 1−5 (Figure 2A), the following two principles that govern the interrelation between the antiaromatic and open-shell characteristics are derived: (1) the mode of the embedded o-quinoidal moiety and (2) the formal molecular symmetry of the ring fusion pattern. The open-shell and closed-shell singlet ground states are attained by the attachment of the o-benzoquinoidal and 1,2-naphthoquinoidal moieties to the pentalene skeleton, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%